Modeling of customer satisfaction in call centers - Aslantaş, Yeliz Leyla. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2010., 2010)
The customer satisfaction becomes a key element in the service sector in the 21st century. Many companies prefer to contact their customers through call centers in order to give service in a cost effective way and retain satisfied customers. The studies in the literature show that efficiency is important since call centers must provide speed of delivery and operate at a low cost to remain competitive. Therefore, managers concentrate on tangible aspects of performance assessment rather than the customer-centric indicators reflecting their satisfaction levels. However, efficiency doesn't imply the customer satisfaction all the time. Thus, this study proposes to examine a call center performance based on two different perspectives: efficiency and effectiveness. It defends that not only better service response rates, but also increased quality of responses are important for customer satisfaction. Therefore, this study suggests that both delivering high service quality and providing an efficient call center management are a must in order to retain customer satisfaction in a call center. In the scope of this study, a methodology is proposed in order to measure the service quality and the performance of call centers. In this context, firstly, the satisfaction level of the customers is measured based on the service they get from the call center. SERVQUAL method is used for determining the gap between the customers' expectations and their perceived quality. Secondly, a simulation model is established in order to simulate the call center's operations. Meanwhile, the most important performance measures determined are monitored within the simulation model. Then, alternative scenarios are performed through simulation experiments for increasing the customer satisfaction level and decreasing the gap between the expectation and perception of service quality of the customers. Results obtained from the simulation experiments are evaluated in order to develop recommendations for the decision makers. The methodology proposed in this study is implemented for a call center of a private bank in Turkey and the application results indicate that the call center has to revise their strategy for achieving its target performance level and for being able to offer a satisfactory level of service quality to its customers.
Keywords: Call centers -- Management.; Consumer satisfaction.